Embryonic exposure to maternal testosterone influences age-specific mortality patterns in a captive passerine bird - Schwabl, Hubert (Springer Netherlands, 2011)
Hormones are potent mediators of developmental programming and maternal epigenetic effects. In vertebrates, developmental exposure to maternal androgen hormones has been shown to impact multiple behavioral and physiological traits of progeny, but the possible consequences of this early exposure in terms of aging-related changes in mortality and fitness remain largely unexplored. Avian eggs naturally contain variable doses of maternal hormones—in particular, androgens—which have documented effects on embryo growth and differentiation as well as adult behavior and physiology. Here, we report that injections of a physiological dose of testosterone (T) into yolks of freshly laid eggs of a small, seasonally breeding songbird, the house sparrow (Passer domesticus), increased survivorship in a semi-natural aviary environment. In addition, survival effects of developmental T exposure were sex-dependent, with males generally having a higher risk of death. Separate analyses for young birds in their first year of life (from hatching up to the first reproductive period the following calendar year) and in adulthood (after the first breeding season) showed similar effects. For first-year birds, mortality risk was higher during the winter than during the period after fledging; for adults, mortality risk was higher during the reproductive than the non-reproductive phase (post-breeding molt and winter). T treatment did not affect nestling body mass, but resulted in higher body mass at 3–4 months of age; T and body mass at this age interacted to influence mortality risk. Embryonic exposure to maternal testosterone may result in lower adult mortality by modifying intrinsic physiological processes involved in health or aging over the lifespan of adult birds. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s11357-011-9222-8) contains supplementary material, which is available to authorized users.